Comparative Analysis of the Seismic Performance between a between a Hysteretic Energy Dissipation System and an Elastomeric Elastomeric Isolation System in Reinforced Concrete Buildings. Reinforced Concrete Buildings (LACCEI, 2024)
This article was carried out in the city of Trujillo - Peru, with the objective of performing a comparative analysis of the seismic behavior between a hysteretic energy dissipation system and an elastomeric isolation system in reinforced concrete buildings, using according to its purpose, an applied type of research, with non-experimental, transversal design and according to its level, descriptive, where the technique for data collection was used direct observation with observation guides and the help of analysis and design software of buildings ETABS V19. 1.0 the data analysis process was carried out through the construction of mathematical models in the aforementioned software, which allowed idealizing the mechanical properties of the structural elements of each building and of the LRB elastomeric isolation devices and SLB energy dissipaters. In order to calculate the structural response of each building, a modal analysis was first performed, obtaining the free vibration periods of the structures with conventional system and with seismic protection systems, as well as a nonlinear seismic analysis Time History considering a maximum earthquake, with a 5% probability of occurrence in 50 years, under the requirements of standards E0.30, E0. 31 and ASCE 7-16 to obtain the behavior of the seismic protection devices, shear, energy dissipation, displacements, accelerations and interstory distortions, with the results it was concluded that as the levels of the structures increase, starting with the eight-story structure, the effectiveness of the isolators is reduced by (3.13%) while the effectiveness of the dissipators increases by (11.56%).